Pengaruh Pendidikan Kesehatan Ibu terhadap Pengetahuan, Sikap dan Perilaku Ibu pada Anak Usia 02-03 Tahun dalam Toilet Training di Paud Bani Salim Baleendah Kabupaten Bandung - Sri Yekti Widadi (Jurnal Health Sains, 2022)
The development of children aged 02-03 years requires better attention, namely with the practice of toilet training conducted by parents, especially mothers who must have knowledge, attitudes and good behavior so that children can carry out independence tasks, especially toilet training. Mothers play an important role in self care activities to be responsible for child independence if the task of independence fails then disturbed which will affect the child, namely regression and detention of urination (BAK) and bowel movements (BAB) this will certainly have an impact on the completion of child development tasks to be disrupted. The purpose of this study is to find out the influence of health education on the knowledge, attitudes and behavior of mothers in children aged 02-03 years in toilet training in PAUD Bani Salim Baleendah Bandung Regency. The research design uses quasy experiment pre-post tests with control groups. Sampling techniques are by purposive sampling consisting of 17 mothers as an intervesi group and 17 mothers as a control group. Data collection tools are questionnaires with health education interventions while data collection tools used are questionnaires. The results showed that based on characteristics in the intervention group and the control group's knowledge, maternal attitudes and behavior improved after being given health education. Health education plays a role in improving the knowledge, attitude and behavior of the mother p value = 0.000. The study recommends giving a booklet that can be used by mothers as a guide in doing toilet training practices at home.